THE CURRENT STATE OF THEORY OF LITERARY TRANSLATION AND TRANSLATION STUDIES IN LANGUAGES OF INDIGENOUS PEOPLES OF RUSSIA - А.A. Arzamazov; I.A. Kulikov (Многоязычие в образовательном пространстве)
The purpose of this study is to highlight the problem of training translators who work with language pairs “the Russian language - a language of indigenous peoples of Russia” and vice versa considering the context of literary translation. The author seeks to systemise and summarise the previous and the current experience in all-Russian translation studies, to emphasise the core issues and suggest possible solutions. A number of scientific works published over the last five years (between 2019 and 2024) is being analysed, as well as other studies which examine the current situation and prospects of literary translation while using the languages of the peoples of Russia. Methodologically, the chronological principle is being implemented to arrange the information related to the topic. Moreover, comparative analysis is being used to distinguish different approaches and researchers’ personal opinions regarding the issues of literary translation. The selection of articles was done through the continuous sampling method. The problems that are being revealed include the decrease in publications of translated works and the lack of specialists in the translation field in question. New trends in translation studies and the need of designing a special terminology are being discussed. It was possible to establish that the current development stage of translation studies in Russia requires a more in-depth study and discussion at the state level. The key conclusion states that the specifics of working with bilinguals and trilinguals should be taken into account and it is essential to provide support for translations of the works written by the peoples of Russia and to form a unified research terminology to describe this kind of translation.